Surface treatment of metals in the plasma of a nanosecond diffuse discharge at atmospheric pressure; The European Physical Journal D; Vol. 71, iss. 5 - Erofeev M. V. Mikhail Vladimirovich; Ripenko V. Vasilii; Shulepov M. Mikhail; Tarasenko V. F. Victor Fedotovich (2017, 2017)
Title screen